Endothelial cell clonality, heterogeneity and dysfunction in pulmonary arterial hypertension - Newcomb, Geoffrey; Farkas, Laszlo (Frontiers in Medicine, 2023)
Our understanding of the pathophysiology of pulmonary arterial hypertension (PAH) has evolved over recent years, with the recognition that endothelial cell (EC) dysfunction and inflammation play an integral role in the development of this disease. ECs within the pulmonary vasculature play a unique role in maintaining vascular integrity and barrier function, regulating gas exchange, and contributing to vascular tone. Using single-cell transcriptomics, research has shown that there are multiple, unique EC subpopulations with different phenotypes. In response to injury or certain stressors such as hypoxia, there can be a dysregulated response with aberrant endothelial injury repair involving other pulmonary vascular cells and even immune cells. This aberrant signaling cascade is potentially a primary driver of pulmonary arterial remodeling in PAH. Recent studies have examined the role of EC clonal expansion, immune dysregulation, and genetic mutations in the pathogenesis of PAH. This review summarizes the existing literature on EC subpopulations and the intricate mechanisms through which ECs develop aberrant physiologic phenotypes and contribute to PAH. Our goal is to provide a framework for understanding the unique pulmonary EC biology and pathophysiology that is involved in the development of PAH.Deleted: not much thought was given for a long time about a potential heterogeneity of ECs within these anatomic localizations…